PERSEPSI AUDITOR DAN MAHASISWA AKUNTANSI TENTANG FUNGSI MICROSOFT EXCEL YANG DIBUTUHKAN UNTUK BERKARIR SEBAGAI AUDITOR (STUDI PADA BPK RI PERWAKILAN PROVINSI SULUT DAN FEB UNSRAT) - Kuyotok, Weni Cikita; Sabijono, Harijanto; Tirayoh, Victorina Z. (Universitas Sam Ratulangi, 2018)
Computer technology is very helpful in the work, one of which is microsoft excel. This study aims to determine which functions of microsoft excel that always used, considered important and need to be mastered for a career as an auditor. The object of research in this research is BPK RI Representative of North Sulawesi Province and Faculty of Economics and Business of Sam Ratulangi University. The method of analysis used in this study is descriptive analysis whose purpose each data collected analyzed and then drawn a conclusion, the type of research used is descriptive quantitative. The results of this study indicate that the basic functions, formats function and filters and sorting data is a function that is always used by auditors. Further basic functions, filter and sorting data, format functions, and keyboard shortcuts are a very important function for the auditor. Finally basic functions, filter and sorting data, format functions and keyboard shortcuts are functions that are highly controlled by auditors. Just keep in mind that for the level of importance, there is a difference between the perceptions of junior team auditors and senior team auditors. The difference is that only senior team auditors think that keyboard shortcuts are a very important function, while junior team auditors think that keyboard shortcuts are limited to important functions only. For accounting students only keyboard shortcuts which is a function that is always used. Furthermore there are six functions that are considered very important by accounting students are basic functions, keyboard shortcuts, format functions, charts and graphs, filter and sorting data, and financial functions. Recent functions that are highly controlled by accounting students are basic functions, keyboard shortcuts and format functions.Keywords: Functions of Microsoft Excel, Auditor, Students